Cervical vestibular-evoked myogenic potentials: norms and protocols - Isaradisaikul S. (2014)
Vestibular-evoked myogenic potential (VEMP) testing is a vestibular function test used for evaluating saccular and inferior vestibular nerve function. Parameters of VEMP testing include VEMP threshold, latencies of p1 and n1, and p1-n1 interamplitude. Less commonly used parameters were p1-n1 interlatency, interaural difference of p1 and n1 latency, and interaural amplitude difference (IAD) ratio. This paper recommends using air-conducted 500 Hz tone burst auditory stimulation presented monoaurally via an inserted ear phone while the subject is turning his head to the contralateral side in the sitting position and recording the responses from the ipsilateral sternocleidomastoid muscle. Normative values of VEMP responses in 50 normal audiovestibular volunteers were presented. VEMP testing protocols and normative values in other literature were reviewed and compared. The study is beneficial to clinicians as a reference guide to set up VEMP testing and interpretation of the VEMP responses.